EVALUASI IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) 2013 PADA PELAJARAN AL-ISLAM DI SD MUHAMMADIYAH 5 JAKARTA - Lismawati, Lismawati (Jurnal Pendidikan Islam, 2016)
Evaluation toward the Implementation of Curriculum 2013 : A Qualitative Study on Elementary School Muhammadiyah 5 Jakarta. Thesis. Research and Educational Evaluation Department, Graduate School of Muhammadiyah University of Prof. DR. HAMKA. January 2015. This Research aims to reveal the evaluation toward the Implementation of Curriculum 2013 by using CIPP (Context, Input, Process, Product) model : A Qualitative Study on Elementary School Muhammadiyah 5 Jakarta. The method used is Evaluation Research Method, that is a method which uses  numbers, written statement, oral information and various facts to obtain data which relates to the problem of evaluation toward the implementation of Curriculum 2013. Data collection used documentation, interviews, and observation. Interviews were conducted at five Muhammadiyah Elementary School Principals, Curriculum Staffs and Classroom teachers Research result concludes that in terms of context, the implementation of Curriculum 2013   in Elementary School Muhammadiyah 5 is clear in its vision, mission and objective. But in term of input, the implementation of Curriculum 2013 is not controlled well yet. It is seen from the input of teachers and employees who are not in accordance with their profession. Some teachers are   classroom teachers who did not graduate from PGSD but from one field of study. The process implementation of Curriculum 2013 is running well, it is in accordance with the procedures established by the government curriculum. There is no   products in the implementation of Curriculum 2013   in Elementary School Muhammadiyah 5 yet, both in academic and non-academic terms. It is very expected for Institutions to pay more attention to the process of recruitment of teachers, therefore the skill of prospective teachers will be in accordance with their profession to gain an optimal learning process. Besides, the institutions is also expected to provide briefing and training to all teachers to be able to master the implementation of curriculum in 2013 correctly and in accordance with the provisions that have been set by the government.